Smart Decoration of Mesoporous TiO2 Nanospheres with Noble Metal Alloy Nanoparticles into Core–Shell, Yolk–Core–Shell, and Surface‐Dispersion Morphologies. Issue 26 (15th August 2014) - Wang, Pengyu; Tooriyama, Hiroko; Yokoyama, Kazuya; Ohtani, Masataka; Asahara, Haruyasu; Konishi, Tomoya; Nishiwaki, Nagatoshi; Shimoda, Masahiko; Yamashita, Yoshiyuki; Yoshikawa, Hideki; Kobiro, Kazuya
Abstract: Noble metal alloy‐decorated spherical mesoporous TiO2 nanoparticles were synthesized by the one‐pot, single‐step reaction of Ti(O i Pr)4, Au 3+, Pt 4+, and Pd 2+ or by the one‐pot reaction of hollow mesoporous TiO2 nanospheres with Au 3+, Pt 4+, and Pd 2+ by means of a solvothermal method in methanol. Au–Pt–Pd@TiO2, Au–Pt@TiO2, and Au@TiO2 mesoporous nanoparticles with core–shell, yolk–core–shell, and surface‐dispersion morphologies were easily constructed. The noble metal alloy cores of the Au–Pt–Pd@TiO2 and Au–Pt@TiO2 yolk–core–shell nanoparticles have Au@Pt–Pd and Au@Pt embedded sub‐core–shell structures, respectively. Abstract : Au–Pt–Pd@TiO2, Au–Pt@TiO2, and Au@TiO2 mesoporous nanoparticles with core–shell, yolk–core–shell, and surface‐dispersion morphologies are synthesized by a solvothermal method in methanol. The alloy cores of the Au–Pt–Pd@TiO2 and Au–Pt@TiO2 yolk–core–shell nanoparticles have Au@Pt–Pd and Au@Pt embedded sub‐core–shell structures, respectively.